Self-management Practices among Women with Type II Diabetic Mellitus and Associated Factors in Al- Diwaniyah City: ممارسات الإدارة الذاتية بين النساء المصابات بداء السكري النوع الثاني والعوامل المرتبطة بها في مدينة الديوانية - Al-Zubaidi, Zahraa Fares; Qasim, Wissam Jabar (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): This study aimed to assess self-management among women with type II diabetes mellitus and associated factors in view of socio-demographic characteristics.Method: A descriptive cross-sectional study conducted at the Diabetes and Endocrinology Center in Al-Diwaniyah City for the period from October 1st, 2022 to April 6th, 2023. The study sample consisted of 200 women who were selected according to the non-probability (purposive) sampling method. The questionnaire items were adopted and developed for the purpose of the study. The total number of items included in the questionnaire was 44 items for evaluating self-management practices of diabetes mellitus type II. Data were collected through interviews and analyzed by applying descriptive and inferential statistical analysis.Results: The study results indicated that the average women age was 51 years. 60% were married, 50% were housewives, 26.5%were illiterate, 60.5%were urban residents and 40.5% had insufficient monthly income. Most (84%) of the study women with type II diabetes mellitus were found to engage in self-management behaviors at a fair (moderate) level (MS= 44.66 ± 9.956). There were statistically significant differences in self-management behaviors among women according to age, monthly income, housing, educational level, and marital status.Conclusions: The results of the current study showed significantly moderate self-management behaviors among women with type II DM diabetes. In particular, diabetic patients were not consistent in regular self-management behaviors as recommended due to lack of awareness regarding self-management practices.Recommendations: An Awareness programs for patients with diabetes who are unmarried, who live in rural areas, or who have low educational levels are recommended in clinical practice to enhance self-management of diabetes.